A beginner's guide to multilevel image thresholding - Rajinikanth, Venkatesan; Raja, Nadaradjane Sri Madhava; Dey, Nilanjan, 1984- (Boca Raton : CRC Press, 2021)
"Choosing appropriate thresholding based on the existing image (Grayscale/RGB) and the assigned task is essential to attain better result and the complexity of the image thresholding is largely reduced with the help of a chosen heuristic algorithm technique. This book emphasizes various image thresholding methods that are necessary for image pre-processing and initial level enhancement. It presents a detailed evaluation, such as choosing the threshold function, need for the heuristic algorithm, choice of objective function, and evaluation of the outcome along with real-time applications in detail"--
OCLC-licensed vendor bibliographic record.
Keywords: Image segmentation; Threshold logic; Imaging systems in medicine; COMPUTERS / Computer Graphics / General; COMPUTERS / Computer Engineering; TECHNOLOGY / Electricity